2011
DOI: 10.1007/s10494-011-9348-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inlet Dilution of Reactants on Premixed Combustion in a Recuperative Furnace

Abstract: This paper presents a numerical study by RANS modeling that investigates the effect of external dilution on the premixed combustion occurring in a recuperative furnace. Calculations are performed using the detailed GRI-Mech 3.0 mechanism to ensure the accuracy of the modeling. Results of the in-furnace flow, temperature, and concentrations of OH, O 2 , CO 2 and NO x are provided. It is found that the external dilution with the inert gas CO 2 plays a significant role in establishing the premixed MILD (Moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…However, chemical effects, such as the addition of H 2 O and CO 2 to NO emission, were observed. The results showed that the reduction in the temperature of beak flame with additional CO 2 is higher than that of the beak flame with additional H 2 O . Diluted fuel (50% natural gas and 50% N 2 ) had an effect on industrial furnaces in highly preheated and diluted air (1273 K with 10% O 2 and 90% N 2 ) combustion.…”
Section: Reduction In Thermal Nox During Flameless Combustionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, chemical effects, such as the addition of H 2 O and CO 2 to NO emission, were observed. The results showed that the reduction in the temperature of beak flame with additional CO 2 is higher than that of the beak flame with additional H 2 O . Diluted fuel (50% natural gas and 50% N 2 ) had an effect on industrial furnaces in highly preheated and diluted air (1273 K with 10% O 2 and 90% N 2 ) combustion.…”
Section: Reduction In Thermal Nox During Flameless Combustionmentioning
confidence: 97%
“…Influence of diluents on temperature uniformity [51]. temperature of beak flame with additional CO 2 is higher than that of the beak flame with additional H 2 O [98][99][100][101]. Diluted fuel (50% natural gas and 50% N 2 ) had an effect on industrial furnaces in highly preheated and diluted air (1273 K with 10% O 2 and 90% N 2 ) combustion.…”
Section: Effect Of Gas Diluentsmentioning
confidence: 99%
“…In practice, MILD combustion is achieved typically by injecting fuel and air into either a recirculating flow or a stream containing hot products. In these configurations, the conditions for MILD combustion are achieved despite the limited time available for the fuel to mix with oxidizer because of the high momentum of the jets (Awosope et al, 2006;Cavaliere and de Joannon, 2004;Dally et al, 2002Dally et al, , 2004Galleti et al, 2007;Katsuki and Hasegawa, 1998;Li and Mi, 2011). Also, there is a possibility to find inhomogeneous mixture containing pockets of unburned and burned gases.…”
Section: Flow Configurationmentioning
confidence: 99%
“…The combustion efficiency is enhanced under MILD conditions due to high preheating temperature using recovered exhaust heat (Cavaliere and de Joannon, 2004;Katsuki and Hasegawa, 1998;Wünning and Wünning, 1997). The thermal NO x formation is suppressed significantly due to low combustion temperature rise and intense dilution (Cavaliere and de Joannon, 2004;Katsuki and Hasegawa, 1998;Krishnamurthy et al, 2009;Li and Mi, 2011;Mohamed et al, 2009;Wünning and Wünning, 1997). Typically, it takes few seconds to produce a substantial amount of thermal NO x at around 1900 K and this reduces to a few milliseconds when the temperature is about 2300 K (Wünning and Wünning, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…According to Li et al [12], high temperature pre-heating of combustion air and the high-speed injection of fuel are the main requirements to achieve MILD combustion condition. Based on these requirements, model flames like the Adelaide Jet in Hot Co-flow (JHC) burner [13] and Delft JHC burner [14,15] were built to emulate MILD condition.…”
Section: Introductionmentioning
confidence: 99%